2013
DOI: 10.1089/brain.2012.0110
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variability in Resting-State Functional Connectivity: Current Status

Abstract: We reviewed the extant literature with the goal of assessing the extent to which resting-state functional connectivity is associated with phenotypic variability in healthy and disordered populations. A large corpus of work has accumulated to date (125 studies), supporting the association between intrinsic functional connectivity and individual differences in a wide range of domains-not only in cognitive, perceptual, motoric, and linguistic performance, but also in behavioral traits (e.g., impulsiveness, risky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 186 publications
(206 reference statements)
4
80
0
Order By: Relevance
“…Connectivity focused analyses of resting-state data have yielded a number of resting-state networks (RSN) which appear to be stable across subjects and time (Damoiseaux et al, 2006). Beyond this overall consistency of topographical features, between-subject variability in spatial network characteristics relating to the involvement of specific brain regions in certain RSN have been linked to various psychiatric disorders, as well as to differences in task performance and behavioural traits (Vaidya & Gordon, 2013). Similarly, variability in the brain's resting activity may be associated with differences in the proneness to cognitive failure.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Connectivity focused analyses of resting-state data have yielded a number of resting-state networks (RSN) which appear to be stable across subjects and time (Damoiseaux et al, 2006). Beyond this overall consistency of topographical features, between-subject variability in spatial network characteristics relating to the involvement of specific brain regions in certain RSN have been linked to various psychiatric disorders, as well as to differences in task performance and behavioural traits (Vaidya & Gordon, 2013). Similarly, variability in the brain's resting activity may be associated with differences in the proneness to cognitive failure.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By correlating spontaneous activity during ā€œresting-statesā€[1], studies of intrinsic brain networks in humans have demonstrated a correspondence with task-related activation patterns[2], relationships to behavior[3], and alterations in processes such as aging[4] and brain disorders[5], highlighting the importance of resting state measurements for understanding brain function. Here, we develop methods to measure intrinsic functional connectivity in Drosophila , a powerful model for the study of neural computation.…”
mentioning
confidence: 99%
“…Furthermore, task fMRI studies point toward aberrant functional interactions between prefrontal control regions and subcortical areas in highly anxious participants (Basten et al, 2011;Bishop, Duncan, Brett, & Lawrence, 2004), and evidence from structural tractography suggests that individual differences in prefrontal-subcortical white matter projections represents a neurostructural correlate of anxiety . Although the insular-opercular network has been most dominantly implicated in anxiety (Vaidya & Gordon, 2013), other resting-state networks such as the frontoparietal control network comprising the dorsolateral prefrontal cortex, medial anterior cingulate, and the intraparietal lobule (Dosenbach et al, 2008) and the default-mode network have also been hypothesized to play a relevant role (Sylvester et al, 2012). Our findings of reduced network efficiency in highly harm-avoidant participants, however, seems to have some specificity for the insular-opercular network: Even though harm avoidance was intercorrelated with the characteristic path lengths of some other networks, these relationships were no longer significant when mean connectivity was taken into account.…”
Section: Discussionmentioning
confidence: 99%